Value relevance and cost of equity capital implications of continuous online voluntary disclosure. - Koh, Li Tiang. (2008)
This paper examines determinants of voluntary disclosures and impacts of disclosure on cost of equity and firm value. Results demonstrated that size of firm, profitability and leverage affect level of on-line disclosure by firms. Results also suggest that markets recognize the value relevance of voluntary online disclosure and analysts following.